Mechanisms of performance degradation in a double-suction centrifugal pump under inflow distortions. (June 2023) - Wang, Wei; Liu, Boxing; Lu, Jinling; Feng, Jianjun; Zhang, Lefu; Luo, Xingqi
Inlet pipes of the centrifugal pump are generally bent to fit in the limited installation space, which can cause inflow distortions for two sides of the double-suction impeller. This study aimed to understand the effect of primary geometric parameters of inlet pipes, including corner angle, straight pipe length downstream of elbow, and turning radius, on pump performance and pressure fluctuations. The pump head, efficiency, and pressure fluctuations were measured for six kinds of inlet pipes in the experiment. Unsteady numerical simulations were performed to understand the flow mechanisms. Results indicate that the bending of inlet pipes is a significant reason for the loss of pump head and efficiency. The penalty on pump performance is augmented by the increase in corner angle, decrease in turning radius, and installation of a short straight pipe downstream of the elbow. Pump efficiency could be maximally reduced by 6.58% with a large corner angle and a small turning radius. The bending of inlet pipes induces pressure imbalance for the two sides of the impeller and increases low-frequency disturbance in the suction chamber, which are responsible for the performance loss. Numerical results reveal that the low-frequency disturbance is caused by the vortex formed in the suction chamber, and the accompanying secondary vortex aggravates the pressure fluctuation synchronously. Parametric studies conclude that the corner angle should be minimized to reduce the penalty on pump performance and pressure fluctuations, and a long straight pipe downstream of the elbow can be installed to decrease vibration for the pump with bent inlet pipes.